pH-Metric Study of Metal-Ligand Stability Constants of Cu(II) and Fe(III) Complexes with Substituted Pyrazole and Isoxazole - G. Potdar, Shashank; Rajput, P.R. (Asian Journal of Chemistry, 2010)
The interaction of Cu(II) and Fe(III) with 3-(2-hydroxy-3,5-dichlorophenyl)-4-benzoyl-5-(2'- furyl)-1-phenylpyrazole (L1) and 3-(2-hydroxy-3,5-dichlorophenyl)-4-anisoyl-5-(2'-furyl) isoxazole (L2) have been studied by Bjerrum method as adopted by Calvin and Wilson. The stability constant of 1 : 1 and 1 : 2 complexes of Cu(II) and Fe(III) have been studied at constant temperature (27 ± 0.1ºC) and 0.1 M ionic strength in 70% dioxane-water mixture. It is observed that formation of 1 : 1 and 1 : 2 complexes is occurring simultaneously.